In Vitro Induction of Pluripotency from Equine Fibroblasts in 20% or 5% Oxygen - de Castro, Raquel V. G. (Stem Cells Int, 2020)
The cellular reprogramming into pluripotency is influenced by external and internal cellular factors, such as in vitro culture conditions (e.g., environmental oxygen concentration), and the aging process. Herein, we aimed to generate and maintain equine iPSCs (eiPSCs) derived from fibroblasts of a horse older than 20 years and to evaluate the effect of different levels of oxygen tension (atmospheric 20% O(2), 5% O(2), or 20% to 5% O(2)) on these cells. Fibroblasts were reprogrammed, and putative eiPSCs were positive for positive alkaline phosphatase detection; they were positive for pluripotency-related genes OCT4, REX1, and NANOG; immunofluorescence-positive staining was presented for OCT4 and NANOG (all groups), SOX2 (groups 5% O(2) and 20% to 5% O(2)), and TRA-1-60, TRA-1-81, and SSEA-1 (only in 20% O(2)); they formed embryoid bodies; and there is spontaneous differentiation in mesoderm, endoderm, and ectoderm embryonic germ layers. In addition to the differences in immunofluorescence analysis results, the eiPSC colonies generated at 20% O(2) presented a more compact morphology with a well-defined border than cells cultured in 5% O(2) and 20% to 5% O(2). Significant differences were also observed in the expression of genes related to glucose metabolism, mitochondrial fission, and hypoxia (GAPDH, GLUT3, MFN1, HIF1α, and HIF2α), after reprogramming. Our results show that the derivation of eiPSCs was not impaired by aging. Additionally, this study is the first to compare high and low oxygen cultures of eiPSCs, showing the generation of pluripotent cells with different profiles. Under the tested conditions, the lower oxygen tension did not favor the pluripotency of eiPSCs. This study shows that the impact of oxygen atmosphere has to be considered when culturing eiPSCs, as this condition influences the pluripotency characteristics.